Children can rate perceived effort but do not follow intensity instructions during soccer training - Reinke, Marco; Schmitz, Gerd (Frontiers in Sports and Active Living, 2023)
The perception of effort is elementary for the self-regulation of exercise intensity in sports. The competence for rating perceived effort (RPE) seems to be related to physical and cognitive development. Children accurately rate perceived effort during incremental exercise tests when loads progressively increase, but it is stillremains unclear how children perform when they participate in sports games, which are characterized by complex tasks with varying intensity profiles. The present study investigates children's competencies for rating perceived effort and producing predetermined intensities during soccer training. Twenty-five children aged 11-13 years performed two similar training sessions. In the first session, the children trained without intensity instructions and continuously rated their effort. In the second session, the children were instructed to realize produce predefined intensities. Before the first training session, executive functions were assessed by cognitive performance tests and a self-report measure. RPE correlated significantly with heart rate measures (R 2 =0.27, p<0.001). As confirmed by factor analysis, iIndividual differences in these correlations were related to the outcomes of the cognitive tests and the self-report measure. RPE in training session 2 differed from RPE in training session 1 (d=1.22, p<0.001), although the heart rate data did not differ significantly between training sessions (d=-0.19, p=0.780). Thirteen-year-old children performed significantly better than eleven-year-old children (d=1.69, p=0.027). The results indicate suggest that children are already able to rate perceived effort during soccer training and that this ability is related to executive functions. In contrast, they do not seem toConversely, children may not be able to alter their intensities in response to instructions, although their ratings suggest that they have largely succeeded in doing so.